Homogenization patterns of the world’s freshwater fish faunas - Villéger, Sébastien; Blanchet, Simon; Beauchard, Olivier; Oberdorff, Thierry; Brosse, Sébastien (Proceedings of the National Academy of Sciences - PNAS, 2011)
The world is currently undergoing an unprecedented decline in biodiversity, which is mainly attributable to human activities. For instance, nonnative species introduction, combined with the extirpation of native species, affects biodiversity patterns, notably by increasing the similarity among species assemblages. This biodiversity change, called taxonomic homogenization, has rarely been assessed at the world scale. Here, we fill this gap by assessing the current homogenization status of one of the most diverse vertebrate groups (i.e., freshwater fishes) at global and regional scales. We demonstrate that current homogenization of the freshwater fish faunas is still low at the world scale (0.5%) but reaches substantial levels (up to 10%) in some highly invaded river basins from the Nearctic and Palearctic realms. In these realms experiencing high changes, nonnative species introductions rather than native species extirpations drive taxonomic homogenization. Our results suggest that the "Homogocene era" is not yet the case for freshwater fish fauna at the worldwide scale. However, the distressingly high level of homogenization noted for some biogeographical realms stresses the need for further understanding of the ecological consequences of homogenization processes.